Influence of Group Dynamics and Performance on Independence of Kosaghra Lestari Farmer Group, Surabaya, East Java - Sabrina Imaniar; Sri Widayanti; Ika Sari Tondang (Universitas Muhammadiyah Palembang, 2025)
This study aims to analyze the influence of group dynamics and group performance on the achievement of independence within the Kosaghra Lestari farmer group in Surabaya City, as a representation of urban agriculture. A quantitative approach was employed, using total sampling of 42 group members. Data were collected through questionnaires, interviews, observations, and documentation, and were analyzed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach, assisted by SmartPLS 4 software. The results indicate that both group dynamics and group performance have a positive and significant effect on group independence, with path coefficients of 0.437 and 0.536, respectively. The R² value of 0.893 suggests that the combination of both variables explains 89.3% of the variance in group independence. Group performance exerts a more dominant influence, particularly in terms of task effectiveness, punctuality, and structured division of responsibilities. These findings underscore the importance of strengthening internal group capacity in fostering sustainable independence, particularly in the context of developing farmer groups in urban settings.